Point-by-point comparisons of permselectivity and fouling-resistance of membranes prepared from blending with di-block and tri-block copolymers. (17th December 2019) - Wu, Tao; Liu, Yang; Zhu, Guo-dong; Li, Zhen-nan; Yi, Zhuan; Liu, Li-fen; Gao, Cong-jie
Abstract: Block copolymers (BCPs) are excellent candidates for surface modification. However, little attention had been directed to systematically investigate the effect of molecular structure on membranes performance, although BCPs of different compositions were extensively blended to membranes before. As a part of this initiative, amphiphilic di-block copolymers (di-BCPs) and tri-block copolymers (tri-BCPs) with similar compositions were synthesized and used as additives for polyethersulfone membranes that were prepared through the non-solvent induced phase separation (NIPS). The chemical composition of the prepared membranes at different depths, the overall morphology and hydrophilicity were comprehensively characterized. The fouling resistance and rejection to proteins of varied charges and sizes were evaluated by using the bovine serum albumin and lysozyme as model molecules. On the basis of the results collected from the above analysis, we found that di-BCPs were superior to tri-BCPs in improving the membrane's permselectivity but inferior to increasing membrane's hydrophilicity and fouling resistance. The reason for this observation was ascribed to their different reservations and segregation that depended on molecular structures. Typically, tri-BCPs tended to reserve in membranes but di-BCPs were easily leaked out during membrane formation. This finding is fundamentally important for the preparation of blend membranes with both higher selectivity and better fouling-resistance. Graphical abstract: Image 1 Highlights: Block copolymers were precisely synthesized and used as additives for membranes. Effects of molecular structure on membranes performance were comprehensively investigated. Membranes prepared from di-block copolymer showed higher rejection. Higher reservation of tri-block copolymers was found. Surface roughness seemed to be slightly dependent on structures of block copolymer.